Sosialisasi Pemahaman manajemen pengelolaan wisata olahraga Pada Desa Sungai Bulian Provinsi Jambi - iwan budi setiawan; Palmizal Palmizal; Adhe Saputra; Alexander Kurniawan; Mhd Usni Zamzami Hasibuan; Rani Astria (Lentera Negeri, 2024)
The service with the title "Socialization of Understanding of Sports Tourism Management in Sungai Bulian Village, East Tabir District, Merangin Regency, Jambi Province" aims to increase community understanding about sports tourism management, especially water tourism. The potential of the lake in the village has not been exploited optimally due to a lack of knowledge about tourism management. This program includes basic training in tourism management, digital marketing, environmental conservation, as well as the application of simple technology such as information boards and tourist guide applications.The results of the service show positive impacts, such as increasing community knowledge in tourism management and safety, strengthening the local economy through tourism activities, increasing tourist attractions with technological innovation, and active community participation in facility management. Scientific publications and participation in seminars expand the reach of this information. It is hoped that this activity can encourage the sustainability of sports tourism management in Sungai Bulian Village and improve the welfare of the local community.Sosialisasi Pemahaman manajemen pengelolaan wisata olahraga Pada Desa Sungai Bulian Provinsi Jambi